MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN FOUNDATIONAL LITERACY AND NUMERACY SISWA SD INPRES 13 RENI AYAU - Muhammad Faizin; Wisnu Wardoyo; Levina Tubur; Syam Kusumaningrum (CV. Adiba Aisha Amira, 2025)
The aim of the study to determine an effect of implementing the Discovery Learning model on developing the Foundational Literacy and Numeracy (FLN) skills of fourth-grade learners at SD Inpres 13 Reni Ayau. The study employed a quantitative method with a Pretest-Posttest Control Group Design experimental approach. The sample consisted of fiveteen learners in the experimental group and seventeen learners in the control group. Data collection techniques included tests, observations, and documentation. The analysis results indicated a significant effect on the improvement of FLN skills in the experimental group after the implementation of the Discovery Learning model. This model encouraged active student engagement, experiential learning, and increased learning independence. Therefore, the Discovery Learning model is effective in enhancing elementary learners' literacy and numeracy skills.